Function of G-Protein-Coupled Estrogen Receptor-1 in Reproductive System Tumors. (29th May 2016) - Qian, Hongyan; Xuan, Jingxiu; Liu, Yuan; Shi, Guixiu
Abstract : The G-protein-coupled estrogen receptor-1 (GPER-1), also known as GPR30, is a novel estrogen receptor mediating estrogen receptor signaling in multiple cell types. The progress of estrogen-related cancer is promoted by GPER-1 activation through mitogen-activated protein kinases (MAPK), phosphoinositide 3-kinase (PI3K), and phospholipase C (PLC) signaling pathways. However, this promoting effect of GPER-1 is nonclassic estrogen receptor (ER) dependent manner. In addition, clinical evidences revealed that GPER-1 is associated with estrogen resistance in estrogen-related cancer patients. These give a hint that GPER-1 may be a novel therapeutic target for the estrogen-related cancers. However, preclinical studies also found that GPER-1 activation of its special agonist G-1 inhibits cancer cell proliferation. This review aims to summarize the characteristics and complex functions of GPER-1 in cancers.